Effects of multiple training modalities in patients with Alzheimer’s disease: a pilot study - Tai SY; Hsu CL; Huang SW; Ma TC; Hsieh WC; Yang YH (Neuropsychiatric Disease and Treatment, 2016)
Shu-Yu Tai,1–4 Chia-Ling Hsu,5 Shu-Wan Huang,5 Tzu-Chiao Ma,6,7 Wen-Chien Hsieh,8,9 Yuan-Han Yang5,7,10,11 1Department of Family Medicine, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung Medical University, 2Department of Family Medicine, Kaohsiung Medical University Hospital, Kaohsiung Medical University, 3Department of Family Medicine, School of Medicine, College of Medicine, Kaohsiung Medical University, 4Research Center for Environmental Medicine, Kaohsiung Medical University, 5Department of Neurology, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung Medical University, 6Graduate Institute of Oral Health Sciences, Kaohsiung Medical University, 7Mentality Protection Center, Fo Guang Shan Compassion Foundation, 8Department of Social Work, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung Medical University, 9Department of Sociology and Social Work, Kaohsiung Medical University, 10Department of Neurology, Kaohsiung Medical University Hospital, Kaohsiung Medical University, 11Department of and Master’s Program in Neurology, Faculty of Medicine, Kaohsiung Medical University, Kaohsiung City, Taiwan Objective: This pilot study investigated the effects of multiple training modalities on cognition, neuropsychiatric symptoms, caregivers’ burden, and quality of life in patients with Alzheimer’s disease (AD).Patients and methods: This intervention study was conducted in 24 patients with AD aged ≥65 years with a Clinical Dementia Rating (CDR) score of 0.5–1. The patients were assigned to receive multiple training modalities (1 hour for each training: Tai Chi, calligraphy, and drawing) over a 6-week period in either the experimental group (n=14) or the comparison group (n=10). A series of neuropsychological tests – namely the Traditional Chinese version Mini-Mental Status Examination, Cognitive Assessment Screening Instrument (CASI), Neuropsychiatric Inventory and the Neuropsychiatric Inventory Caregiver Distress Scale, and the Clinical Dementia Rating Sum of Boxes scale – were conducted at the baseline and after the intervention. The World Health Organization Quality of Life-BREF (WHOQOL-BREF) and Zarit Caregiver Burden Scale were used to assess the quality of life and caregivers’ burden, respectively. Independent sample t-test and paired sample t-test were used to analyze the data.Results: After the intervention, the experimental group reported higher scores in the orientation domain of CASI (P=0.007) and in the psychiatry domain of WHOQOL-BREF (P=0.042) compared with the comparison group. Caregivers’ distress was significantly decreased in the experimental group (P=0.035) but not in the comparison group (P=0.430).Conclusion: The multiple training modalities improved scores in the orientation domain of CASI and psychiatry domain of WHOQOL-BREF in patients with AD. Moreover, the intervention reduced caregivers’ distress. Keywords: multiple training modalities, Alzheimer’s disease, quality of life, cognitive function, caregivers’ burden